Opportunities and Challenges of MSME Marketing in the Digital Era (Pusat Riset dan Inovasi Nasional, 2025)
Micro, Small, and Medium Enterprises (MSMEs) frequently encounter challenges in adopting digital marketing strategies due to limited internal resources and external constraints. This study aims to analyze the opportunities and challenges of MSME marketing in the digital era by examining the influence of internal and external factors on digital transformation. Using a quantitative approach, data were collected from 180 MSME entrepreneurs in Surakarta through structured questionnaires and analyzed using statistical methods. The findings indicate that both internal factors, such as human resources, digital skills, and organizational readiness, and external factors, including market dynamics and technological infrastructure, significantly affect the level of digitalization. However, internal factors emerge as the most dominant predictors and serve as the fundamental driver of digital marketing transformation. The study also reveals that MSMEs implementing digital marketing experience higher-than-average online sales performance. These results suggest that strengthening internal resource capacity is essential for enhancing digital adoption. Therefore, MSME development policies should prioritize capacity-building programs to ensure sustainable competitiveness in the digital economy.